Application of Management Aspects in Business in Beef Cattle Group - Fitrimawati Fitrimawati; Nurhayati Nurhayati; Ida Indrayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Community service was conducted at the Balai Gadang Sapan livestock group in the Rambatan sub-district, Tanah Datar district. This group's businesses are beef cattle breeding and organic fertilizer processing. The problem with group businesses is that management and business knowledge still need to be higher. Group members still need help to apply management and business principles in managing the business. This community engagement aims to develop the Balai Gadang Sapan group business by increasing the performance and productivity of the beef cattle breeding and organic fertilizer processing business (UPPO) through implementing management aspects in the group business. The methods for carrying out activities were lectures, discussions, mentoring, and demonstrations. The stage carried out in implementing those four methods was the preparation stage, namely preparing material related to completing the solution in the form of PowerPoint, modules, banners, and leaflets. At the implementation stage, modules were distributed to participants, and the material was later. The evaluation stage involved participants filling out a prepared questionnaire. This evaluation was carried out to determine the group's ability to implement management aspects. The results of this activity were five essential aspects that must be applied in group management: making plans consisting of learning and business planning, organizing, and carrying out activities, evaluating business activities, and cadre of management. The group's ability to apply management aspects can be improved at the intermediate and primary levels.